Perbandingan Keputusan Rujuk Pasien Stroke Baru Dengan Pasien yang Pernah Didiagnosis Sebelumnya Pada Layanan Telemedis - Prawiroharjo, Pukovisa; Kurniawan, Mohammad; Alexander, Fooann (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
ABSTRACT Introduction: Stroke is the third leading cause of death worldwide. Unfortunately, the high incidence of stroke in Indonesia is not matched by prompt and effective treatment, resulting in a high disability rate. These limitations make decision-making in telemedicine services challenging. Objective: This study aims to compare decision-making related to stroke management between newly diagnosed patients and those previously diagnosed. Methods: This study employed a cross-sectional retrospective design. The data consisted of 256 secondary data obtained from telemedicine company conversations during March and April 2020. Patients were categorized into newly diagnosed stroke patients and previously diagnosed stroke patients. Results: Among the 256 subjects, a significant relationship was found between patient status and decisions regarding referral and pharmacological management. Newly diagnosed stroke patients more frequently received referral decisions, while previously diagnosed patients more often received pharmacological management. Discussion: This study indicates a significant association between patient status and decisions on referral and pharmacological management in telemedicine services. Further studies with larger sample sizes and longer time periods are needed for better representation of conditions in Indonesia. Keywords: patient status, pharmacological treatment, referral, stroke, telemedicine.